Factors Affecting Entrepreneurial Interest in Sharia Insurance Students at the State Islamic University of North Sumatra - Rina Aldila; Zuhrinal M. Nawawi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
In this day and age, many college graduate students need a long time to get a job, so there are still many unemployed students from various college graduates. Entrepreneurship is the key to overcoming the unemployment of college graduates. For this reason, student interest in running a private business is needed to be developed on campus. Entrepreneurship is a field that is often discussed because it is always experiencing developments in the economic and business fields. Entrepreneurship is considered an important aspect because one of the solutions to help the economy in Indonesia is by increasing the number of competent entrepreneurs, entrepreneurs are people who will always face risks and are smart in looking for opportunities. Higher education is an institution that is expected to be able to give birth to young entrepreneurs through organized entrepreneurship education. This research is a qualitative method with a literature review. There are several factors found regarding the factors that make students want to be entrepreneurs such as variables, namely, entrepreneurship lessons, family environment, self-confidence, income expectations, encouragement, business capital, technology.